Optimization of suitable auxin application in a recalcitrant woody forest plant of Eurycoma longifolia (Tongkat Ali) for callus induction - Mahmood, Maziah; Normi, Rosli; Subramaniam, Sreeramanan (Academic Journals, 2010)
A study was carried out to determine and optimize suitable auxin for callus induction in Eurycoma longifolia. The induction of callus cultures using leaf, petiole, rachis, stem, tap root, fibrous root, cotyledon and embryo segments were successfully achieved by using various auxins such as 2,4-D, IAA, NAA, picloram and dicamba. The cultures were observed daily for one month. The overall results from the experiments showed that the presence of 2,4-D was the most suitable auxin for the highest callus induction and growth performance rate by using various explants types of E. longifolia. The callus initiation in leaf explant was the highest using 1.0 mgL-1 of 2,4-D (81.67%), followed by picloram (78.33% at 3.0 mgL-1), dicamba (73.33% at 2.0 mgL-1) and NAA (61.67% at 4.0 mgL-1). Auxin, 2,4-D and picloram at 4.0 mgL-1 were found to be the most effective for callus induction (78.33%) using petiole explant. It was followed by using dicamba (73.33% at 2.0 mgL-1), NAA (73.33% at 3.0 mgL-1) and IAA (61.67 % at 3.0 mgL-1), respectively. In addition, the percentage of callus induction from rachis was obtained at highest rate by using picloram (86.67 % at 4.0 mgL-1), followed by 2,4-D (81.67% at 4.0 mgL-1), dicamba (78.33% at 2.0 mgL-1), NAA (58.33% at 2.0 mgL-1) and IAA (45% at 3.0 mgL-1). Meanwhile, for stem explant, it has been noticed that highest callus induction at 88.33% could be obtained from medium containing 2,4-D at 2.0 mgL-1, followed by picloram (80% at 5.0 mgL-1), dicamba (85% at 5.0 mgL-1), NAA (76.67% at 1.0 mgL-1) and IAA (63.33% at 4.0 mgL-1). For tap root explant, the highest amount of callus was formed at 3.0 mgL-1 2,4-D and 1.0 mgL-1 picloram (81.67%), followed by dicamba (78.33% at 1.0 mgL-1). For fibrous root explant, the highest callus was produced in 2,4-D at 4.0 mgL-1 (86.67%), picloram (78.33% at 1.0 mgL-1) and dicamba (78.33% at 2.0 mgL-1). The highest scoring of callus induction from cotyledon was determined by using 2,4-D at 4.0 mgL-1 (85%), followed by picloram (83.33% at 1.0 mgL-1), dicamba (78.33% at 2.0 mgL-1), NAA (56.67% at 1.0 mgL-1) and IAA (36.67% at 3.0 mgL-1). Finally, the highest scoring for callus induction from embryo was produced in 2, 4-D and picloram at 2.0 and 5.0 mgL-1 (both 85%) followed by NAA and IAA 83.33% at 1.0 and 4.0 mgL-1, respectively, and dicamba, 81.67% at 5.0 mgL-1. The percentages of callus induction using various types of explants were found to be increased significantly by using selected types of auxins in E. longifolia plants.